2008
DOI: 10.1016/j.autneu.2008.01.006
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac autonomic control and the effects of age, race, and sex: The CARDIA study

Abstract: Background-Stratification variables of age, race, and sex figure prominently in the assessment of cardiovascular disease risk. Similarly, cardiac autonomic regulation, measured by RR interval variability (RRV), is associated with risk. The relationship among these variables is unclear.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

10
36
1
1

Year Published

2009
2009
2014
2014

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(48 citation statements)
references
References 50 publications
10
36
1
1
Order By: Relevance
“…Regarding the gender differences in untrained rats, our results showed reduced sympathetic tonus and improved baroreflex sensitivity in female rats compared to previous studies on male rats (7,23,32), corroborating human data that showed sympathetic predominance in men compared to women (14,15,33). In fact, Chen and DiCarlo (16) demonstrated that female rats had a higher maximum baroreflex gain (40%) than male rats, and daily spontaneous running attenuated the arterial baroreflex regulation of HR in both sexes.…”
Section: Discussionsupporting
confidence: 78%
“…Regarding the gender differences in untrained rats, our results showed reduced sympathetic tonus and improved baroreflex sensitivity in female rats compared to previous studies on male rats (7,23,32), corroborating human data that showed sympathetic predominance in men compared to women (14,15,33). In fact, Chen and DiCarlo (16) demonstrated that female rats had a higher maximum baroreflex gain (40%) than male rats, and daily spontaneous running attenuated the arterial baroreflex regulation of HR in both sexes.…”
Section: Discussionsupporting
confidence: 78%
“…We noted no racial differences in baseline heart rate variability or BRS. Although some studies have shown reduced high-frequency power of heart rate variability and lower BRS in African Americans (58), this is not a universal finding, with several studies noting no racial differences (14,30,47). Since within single individual markers of tonic vs. reflex vagal activity could have variable predictive power, Vanoli et al (52) have recently proposed a composite index derived from heart rate variability and BRS that gives equal weight to both the tonic and reflexive nature of cardiac autonomic physiology.…”
Section: Discussionmentioning
confidence: 90%
“…The lower risk of AF in blacks has been potentially attributed in part to possible racial differences in left atrial size, 23 cardiac autonomic tone, 27 and genetic differences. 28,38 In 711 patients in the Heart and Soul study who underwent echocardiography while in sinus rhythm, 23 although ventricular and atrial volumes were similar in white and black participants, whites had a slightly larger anterior-posterior left atrial diameter after adjusting for potential confounders.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, traditional risk factors appear to have similar strengths of association with new AF in blacks and whites, despite the lower risk of AF in blacks. 21,22 The lower risk of AF in blacks has been potentially attributed in part to possible racial differences in left atrial size, 23 cardiac autonomic tone, 27 the sensitivity of methods used to detect AF, 20 and underascertainment of AF in blacks, 21 possibly because of potential differences in access to care. Recent work has also suggested that the lower risk of AF in blacks may be in part attributable to genetic factors, with an increased estimated degree of European ancestry in blacks associated with an increased risk of incident AF.…”
Section: Original Articlementioning
confidence: 99%